Osteonecrosis of the jaw in patients with multiple myeloma treated with bisphosphanates - Pavkovic M; Petrusevska G; Jovanovic R; Karanfilski O; Cevreska L; Stankovic S; Stojanovic A (Македонска академија на науките и уметностите, Одделение за биолошки и медицински науки = Macedonian Academy of Sciences and Arts, Section of Biological and Medical Sciences, 2010)
Bisphosphonates are pyrophosphate analogues which inhibit osteoclastic activity. Long term use of bisphosphonates has recently been associated with osteonecrosis of the jaw (ONJ) defined as a three month non-healing defect in the jaw. ONJ is commonly precipitated by a tooth extraction or other stomatological procedure in patients treated with long-term, potent, high dose intravenous bisphosphonates for the management of myeloma, breast or prostate cancer. The aim of this study was to evaluate the incidence of ONJ in patients with MM treated with bisphosphonates during the last 8 years in our institution and to pre-sent the first two cases. We have analysed 247 myeloma patients diagnosed in our institution in the period 2002-09. Only 190/247 patients (76.9%) were treated with bisphosphonates. The incidence of ONJ in our group of patients treated with bisphosphonates was 2/190 (1%). The most commonly used bisphosponate was i.v. pamidronate (17.8%) and 46.6% were treated with two or more types of bisphosphonates. Sixty-five patients (34.2%) received oral forms of bisphosphonates; 42.1% patients were treated with i.v. forms of pamidronate, ibondronate or clodronate, and 45 patients (23.7%) received a combination of oral and i.v. forms of bisphosphonates. The mean duration of bisphosphonates therapy was 24.7±17.7 months. The low incidence of ONJ in our institution could be explained by the rare use of zolendronate, which is the most commonly referred bisphosphonate causing ONJ, and by a relatively shorter duration of bisphosphonates treatment in patients with MM. Despite the fact that ONJ is a rare complication in our institution, preventive measures must be considered.